Peran Komunikasi Efektif dan Efisien dalam Interaksi Belajar Mengajar - Kaharuddin; Hajar, Sitti; Nasir; Marwan, Andi; Andini; Nuraeman; Kaharuddin, Kaharuddin (Elementary Journal : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
As social creatures and living in groups in everyday life, humans certainly do not escape interaction or communication. Communication is the process of conveying a message from the communicator to the communicant or audience, whether in the form of symbols or emblems, in the hope of bringing or understanding the message to students (students) in the classroom or in society and trying to change attitudes and behavior. In the world of education, the learning process will be effective if communication and interaction between teachers and students occurs efficiently and effectively. In classroom learning, the communication process will take place either between teacher and student, in this case, students or vice versa between students and teachers or educators, where the learning material is the message in the learning communication process which is often seen as the heart or core of learning activities. In this learning communication, educational interactions occur which take place in the form of message exchange which is none other than learning material. In the context of learning communication, teachers are placed in a position as communicators because the duties and roles of teachers as learning leaders position them as communicators, while students are placed as communicants or students. Teachers must be able to master good interaction patterns and communication techniques in the learning process.